ABCD-Based Mentoring in the Application of the Quranic Method for 8-Year-Old Students at TPQ Al-Muttaqin: A Case Study of the Potential of Inspirational Students in Pondok Wuluh Village - Hanifa Hanifa; Andini Afiatus Sholehah; Arfiyani Wulandari; Famei Haqqi Adi Putra; Robiatul Adawiyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This community service project analyzes the effectiveness of Asset-Based Community Development (ABCD) mentoring in applying the Quranic method to improve the motivation and fluency of 8-year-old students at the Al-Muttaqin Islamic Boarding School (TPQ) in Pondok Wuluh Village. The activity was motivated by the students' varying reading abilities, with one inspiring student demonstrating more rapid reading progress. This student's potential was utilized as a local asset to motivate their peers. The mentoring session was conducted over ten meetings, involving TPQ teachers, student guardians, and the community. The ABCD stages included asset identification (discovery), dream formulation (dream), design (design), implementation (define & deliver), and sustainability evaluation (destiny). Data were collected through participant observation, in-depth interviews, and documentation, then analyzed qualitatively. The results showed significant improvements in reading fluency and learning motivation. The inspiring student served as an effective role model, while community support strengthened the program's sustainability. These findings confirm the ABCD approach as an appropriate strategy for community-based empowerment in Quranic education.